Consensus on methods of development of clinical practice guidelines in oncology under the auspices of Maria Sklodowska-Curie National Research Institute of Oncology and the Agency for Health Technology Assessment and Tariff System - Jan Walewski; Dominik Dziurda; Mariusz Bidziński; Barbara Bobek-Bilewicz; Marek Dedecjus; Iwona Hus; Beata Jagielska; Jacek Jassem; Andrzej Kawecki; Dariusz Kowalski; Magdalena Krasztel; Maciej Krzakowski; et al. (Nowotwory, 2022)
INTRODUCTION: As the changes leading to improvement of cancer care in Poland have shown the need to introduce clinical practice guidelines into the health care system, it has become clear that no methodological standard of the process for guidelines preparation has been established so far. The following process aims to present a unified and comprehensive clinical practice guidelines (CPGs) development methodology. MATERIALS AND METHODS: A review of globally recognised methods used by guideline development groups was prepared, informing the discussion during three plenary meetings and extensive consultations in writing. The resulting document was unanimously approved by a group of 24 methodologists and clinical experts, and has been formally recognized as a standard for CPGs development by the management of the National Institute of Oncology and the Agency for Health Technology Assessment and Tariff System. RESULTS: Within the process, 43 recommendations were formulated to create unified and comprehensive rules for guideline development within the Polish healthcare system. CONCLUSIONS: The presented methods are consistent with the globally recognized tools and methods of guideline development, such as GRADE and ADAPTE, and follow quality criteria described by AGREE II. The process supports the development of high-quality guidelines within a resource-constrained setting by allowing to choose between adoption, adaptation, or de novo development of either the whole document of guidelines or particular recommendations.